2008
DOI: 10.1063/1.3026173
|View full text |Cite
|
Sign up to set email alerts
|

Similarities in the kinetics of photocrystallization and photodarkening in a-Se

Abstract: Comparative study of the photodarkening relaxation-kinetics in amorphous selenium for above-bandgap and sub-bandgap illumination Appl. Phys. Lett. 105, 051912 (2014); 10.1063/1.4892836 Nanocrystallization of amorphous M-Si thin film composites (M=Cr, Mn) and their thermoelectric properties AIP Conf.Influence of the plasma pressure on the microstructure and on the optical and mechanical properties of amorphous carbon films deposited by direct current magnetron sputtering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Using a double-well energy configuration, it was shown that the energy barrier between the ground state and a metastable state in pure a-Se was 0.8 eV [2]. A similar activation behavior was observed in photo-induced crystallization (PC) of a-Se studied by Raman spectroscopy [3]. This similarity suggests that the formation kinetics of PD and PC are controlled by the same configurational changes occurring via photo-induced metastable defects.…”
Section: Introductionmentioning
confidence: 61%
“…Using a double-well energy configuration, it was shown that the energy barrier between the ground state and a metastable state in pure a-Se was 0.8 eV [2]. A similar activation behavior was observed in photo-induced crystallization (PC) of a-Se studied by Raman spectroscopy [3]. This similarity suggests that the formation kinetics of PD and PC are controlled by the same configurational changes occurring via photo-induced metastable defects.…”
Section: Introductionmentioning
confidence: 61%
“…Illuminated Se samples were found to be partially crystallized, which may present the photo-enhanced crystallization, being known for Se for a long time [15,16]. However, no appreciable anisotropic structures were detected.…”
Section: Resultsmentioning
confidence: 84%
“…Therefore, we suggest that experimentally observed crystallization of the a-Se samples under subband-gap illumination [7,30] should be linked to the double-electron excitation process.…”
Section: Photoinduced Lattice Relaxationmentioning
confidence: 92%
“…The direct evidence of the valence alteration in a-Se is experimentally detected unpaired electrons which appear under light illumination [2]. It is believed that the VAP defects are responsible for many of the photoinduced effects including photodarkening (PD) [6][7][8], photoinduced crystallization [7] and volume expansion [9][10][11] as they induce the subband gap defect states [12][13][14][15] . Although a link between these effects is not confirmed with direct experiments, they all have similar kinetics and are shown to be thermally activated processes with similar activation energies around ∼0.9 eV [6,7] -the value which was suggested for the VAP defect relaxation [16].…”
Section: Introductionmentioning
confidence: 99%